Lavado endoscópico con colocación de catéter trans acueducto de Silvio en paciente lactante con ventriculitis de difícil manejo - Alejos CB, Maldonado; L, Grisotto; Colombo, G; Gómez Ávalos, JM; Bustamante , JL; D´Agustini , MO (Revista Argentina de Neurocirugía, 2020)
Introduction: Ventriculitis represents an infectious emergency which is normally associated with neurosurgical procedures. The incidence is unknown due to the variation of the diagnostic criteria. Case description: We present a 6-month-old female patient with a history of post-hemorrhagic hydrocephalus. The patient was diagnosed with Enterobacter complex ventriculitis difficult to manage associated with peritoneal ventricular shunt (VP). The patient received combined antibiotic treatment with Meropenem intravenous and intravenous-intraventricular Colistin associated with endoscopic treatment. This endoscopic treatment consisted of washes, aspiration of the intraventricular purulent content, third endoscopic ventriculostomy (ETV), bilateral coagulation of the choroid plexus and aqueductoplasty with external ventricular drain catheter (EDV). This EDV was placed between the third and fourth ventricle in order to maintain its permeability so as to ensure the arrival of intraventricular antibiotics to the fourth ventricle. Discussion: Ventriculitis is associated with multiple complications and a high morbidity and mortality rate. The treatment of ventriculitis that is difficult to manage is still controversial. Currently several authors show good results of endoscopic lavage treatment associated with combined intravenous/intraventricular antibiotic treatment. This leads to greater intraventricular antibiotic concentrations. Conclusion: We consider that combined treatment has been successful for ventriculitis difficult to manage. In those cases, with obstruction of the Silvio aqueduct, it is recommended to perform aqueductoplasty and placement of a multi-fenestrated catheter; to maintain patency and the arrival of antibiotics in the fourth ventricle.